Aortic root dilatation among young competitive athletes: echocardiographic screening of 1929 athletes between 15 and 34 years of age - Kinoshita, N.; Mimura, J.; Obayashi, C.; Katsukawa, F.; Onishi, S.; Yamazaki, H. (American Heart Journal, 2000)
BACKGROUND: Aortic dilatation can be lethal for young competitive athletes. The prevalence among athletes is not known, however, and thus a reasonable approach to early recognition remains uncertain. METHODS AND RESULTS: Echocardiograms of 1929 normotensive athletes 15 to 34 years of age were analyzed. Five (0.26%) athletes had aortic dilatation; 4 of the 5 played basketball. This made the prevalence of aortic dilatation 0.96% (4 of 415) among basketball and volleyball players, who represented a population of especially tall athletes. Tallness aside, only 2 of the 5 athletes had features of Marfan syndrome. Among the athletes without aortic dilatation, the relation between body surface area and aortic root dimension was nonlinear and best described with a quadratic regression model. Athletes with aortic dilatation fell well outside the 95% confidence interval. CONCLUSION: Because a higher incidence of aortic dilatation is to be anticipated among very tall athletes, inclusion of echocardiography in screening before participation in certain sports should be considered.